MATHEMATICAL REPRESENTATION ABILITY OF PROSPECTIVE MATHEMATICS TEACHERS IN SOLVING TRIGONOMETRIC PROBLEMS - Margaretha Madha Melissa; Laurentius Anindito Wisnu Susanto; Aldila Nindya Puspita; Samsul Vandam Sigalingging (KALAMATIKA Jurnal Pendidikan Matematika, 2023)
This study aims to investigate the proficiency of prospective mathematics teacher students in mathematical representation. To achieve this goal, we used a qualitative research design with a descriptive approach. The research subjects consisted of three undergraduate students from Mathematics Education department at a private university in Yogyakarta. Data were collected using a test for mathematical representation ability and interviews. The data were analysed descriptively using techniques by Miles and Huberman. It shows that the mathematical representation ability of prospective teacher students was in low category. This can be seen from the average achievement of indicators of mathematical representation ability (34.74%). The ability to create and use representations for collecting/organizing, recording, and communicating mathematical ideas is 33.33%. The ability to select, apply and translate various forms of representation mathematics to solve problems is 29.76%. And the ability to use multiple representations is 41.11%.